PENGARUH DESAIN KERJA DAN STRES KERJA TERHADAP KUALITAS KERJA GURU SD NEGERI DI KECAMATAN CAKUNG, JAKARTA TIMUR - Yuni Siskawati (Universitas Negeri Jakarta, 2015)
The purpose of this research is to determine the effect of work design and work stres on work quality in this study teacher elementary school disctric cakung. The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) work design has a positive direct effect in work quality, (2) job stres has a negative direct effect in quality work, (3) design work has a negative direct effect in job stress.